20th International Conference on Silicon Carbide and Related Materials (ICSCRM 2023) - Michele Riccio; Andrea Irace; Giovanni Breglio (Trans Tech Publications Ltd, 2024)
Selected peer-reviewed extended articles based on abstracts presented at the 20th International Conference on Silicon Carbide and Related Materials (ICSCRM 2023)Aggregated Book